The Impacts Of Simplicity Factors On The Aesthetic Value Of Heritage Interior Space: The Case Of Shophouses In Georgetown – Penang - Abdulqader, Oday Qusay; Ibrahim, Fuziah; Bahauddin, Azizi (Universiti Sains Malaysia, 2016)

(untitled)
To create simple interior space within heritage building is a tricky challenge. Simple space dose not means scanty design, conversely, simple design in heritage area consists a profound meanings and reflects the original aesthetic value of that space. The design of shophouse as a formation is simple raw building, contained three to four main zones. While, shophouse interior space reflects the value of community and rich culture by using simplicity as a factor to present the complex feelings and meanings in one place. Georgetown is the capital city of Penang, Malaysia, which populated by harmonized mixture of communities, this mix-culture influent the architecture and interior style of the city. As a result, eclectic architecture style created and become a staples of Georgetown. Therefore, it listed as World Heritage City in 2008 by UNESCO. The current research is to clarify the relationship between simplicity and aesthetic in interior design of heritage building. Thus, the study is qualitative mode including semi-structured interview questions, the responders were the users, owners and staff of coffee shops in heritage shophouse. As well as, observation, behavioral mapping are used to collect the data for the shophouses and users reaction. Aesthetic value does not depend on the complex design, high quality material and form. Good places should be simply understood with high familiarity value. Additionally, shaped grate space should harmonized between users' needs and identity of the place.